Reflective accounts of psychiatry in Australasia, 1963–2000. (April 2013) - Lawrence, Joan; White, Richard; O'Connor, Nick; Robertson, Michael
Objective: To provide reflective accounts of psychiatry through the first four decades of the existence of the Royal Australian and New Zealand College of Psychiatrists (RANZCP). Conclusions: The period from the 1960s to the end of the millennium saw significant changes in both the craft of psychiatry and the social and cultural context in which specialist training in psychiatry occurred.